(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Corporate governance is not a goal in itself, but seeks to improve the performance of companies and ensure their access to capital at a reasonable cost, and that there is a relationship between governance and the degree of economic performance of the company, companies that enjoy good governance have good managers and good transparency and will inspire confidence to investors. The audit committee represents one of the axes on which good governance is based, as the lack of an effective audit committee may achieve reform, but it will be deficient, which imposes the need to make efforts to activate the role of the audit committee in local joint stock companies, which contributes to strengthening governance practices and implementation mechanisms. It requires the efforts of many parties, especially the Iraq Stock Exchange and the Registrar of Companies, to follow up on the companies’ compliance with the provisions of the legislation issued related to the Audit Committee and to reconsider them for the purpose of activating this on the one hand. The proposal for the structure and practices of the audit committee in Iraqi joint stock companies, which is an important step to clarify the essence of the audit committee and enhance its role in implementing corporate governance.